Management of insect pests of tomato (Solanum lycopersium L.) and okra (Abelmoschus esculentus L.) using karate (lambda cyhalothrin) with alata samina - Zomonway, Eddie Zorkpo (2016)
A thesis submitted to the Department of Crop and Soil Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana in partial fulfillment of the requirements for the Degree of Master of Philosophy in Crop Protection (Entomology)